إعلام المواطن عبر مواقع التواصل الاجتماعي (Comprehensive Journal of Science, 2026)
The research concluded that citizen journalism via social media is no longer a marginal practice carried out by ordinary individuals; rather, it has become an active popular pattern within contemporary media, due to its influence—especially in environments suffering from weak official media institutions and security and political instability, as is the case in Libya. The study showed that the social media platforms examined in this research do not only act as intermediaries for transmitting events and information, but also directly contribute to shaping the content of news and its narrative formulation. These platforms also determine the extent of its spread according to the characteristics of each platform and their algorithmic mechanisms.It was found that Facebook is the most popular and widely used platform in the context of citizen journalism in general, and the Libyan model in particular, especially regarding the circulation of local news. Community pages emerged as alternative sources of news, particularly given the limited access to information from official authorities. This was confirmed in most studies that dealt with social media, in which Facebook ranked first. Conversely, Twitter (X) plays a prominent role in guiding public discussion and setting the agenda, particularly concerning political and security issues, through hashtags and elite interaction, despite the limited dissemination of news on it compared to other platforms.Regarding Instagram and TikTok, their presence in studies of Arab and international citizen journalism was limited, as they were often examined within the general framework of digital or alternative media. This is despite their increasing use in transmitting fast visual content during crises and breaking events, due to the nature of these platforms, which are based on visual images and short videos, accompanied by event summarization and the predominance of emotional dimension over analytical focus.The research also concluded that differences between platforms do not imply differences in the event itself; rather, the difference is reflected in how the event is presented and circulated. A single event may appear as documented news on one platform, a public discussion on another, and interactive visual content on a third. This highlights the multifaceted nature of citizen journalism via social media in terms of its ability to reproduce the same event in different forms across platforms, each carrying its own distinctions. This was revealed in applied models such as the case study of the Libyan Chief of Staff plane crash; citizen journalism contributed to the rapid transmission of the event, while at the same time numerous limitations appeared, especially regarding objectivity and accuracy in reporting, as well as the circulation of preliminary, incomplete information. This confirms the dual nature of this populist media pattern, which oscillates between contributing to coverage and facing professional and ethical challenges that it often lacks.Nonetheless, despite all this, citizen journalism has become an integral part of new media work. Today, it is an undeniable reality that cannot be ignored or bypassed. Restrictions on press freedom have further reinforced its extensive presence in the current media landscape.
Keywords: Citizen journalism – Alternative media – Participatory media – Digital media – Social media – News circulation – Public interaction.